The Effect of Price, Location, and Service Quality on Customer Satisfaction at AA. Motor Service Surabaya - Minanti Dwi Setianingrum; Siti Ning Farida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of price, location, and service quality on customer satisfaction among consumers who purchase products or use services at AA Motor Service Surabaya. The research employs a quantitative approach with data collection conducted through questionnaires. The study population consists of residents of Surabaya who have made transactions at AA Motor Service Surabaya, with a sample of 89 respondents selected using the purposive sampling technique. The respondent criteria include consumers from Surabaya who have used the service at AA Motor Service Surabaya at least once in the last three months. Data analysis was performed using the Statistical Program for Social Science (SPSS) version 26. The findings indicate that price, location, and service quality simultaneously have a significant effect on customer satisfaction at AA Motor Service Surabaya. Partially, the variables of price and service quality significantly influence customer satisfaction. Conversely, the location variable does not have a significant partial effect on customer satisfaction.